A multicenter retrospective study of 223 patients with t(14;16) in multiple myeloma. Issue 5 (29th February 2020) - Goldman‐Mazur, Sarah; Jurczyszyn, Artur; Castillo, Jorge J.; Waszczuk‐Gajda, Anna; Grząśko, Norbert; Radocha, Jakub; Bittrich, Max; Kortüm, K. Martin; Gozzetti, Alessandro; Usnarska‐Zubkiewicz, Lidia; Davila Valls, Julio; Jayabalan, David S.; et al.
Abstract: The t(14;16) translocation, found in 3%‐5% of newly diagnosed (ND) multiple myeloma (MM), has been associated with adverse outcomes. However, the studies establishing the characteristics of t(14;16) included solely small cohorts. The goal of the current international, multicenter (n = 25 centers), retrospective study was to describe the characteristics and outcomes of t(14;16) patients in a large, real‐world cohort (n = 223). A substantial fraction of patients had renal impairment (24%) and hemoglobin <10 g/dL (56%) on initial presentation. Combined therapy of both immunomodulatory drug and proteasome inhibitor (PI) in the first line was used in 35% of patients. Autologous stem cell transplantation was performed in 42% of patients. With a median follow up of 4.1 years (95% CI 3.7‐18.7), the median progression‐free survival (PFS) and overall survival (OS) from first line therapy were 2.1 years (95% CI 1.5‐2.4) and 4.1 years (95% CI 3.3‐5.5), respectively. Worse OS was predicted by age > 60 years (HR = 1.65, 95% CI [1.05‐2.58]), as well as revised International Scoring System (R‐ISS) 3 (vs R‐ISS 2; HR = 2.59, 95% CI [1.59‐4.24]). In conclusion, based on the largest reported cohort of t(14;16) patients, quarter of this subset of MM patients initially presents with renal failure, while older age and the R‐ISS 3 predict poor survival.